Adopting Emerging Technology To Promote Circular Economy in the Built Environment - Berawi, Mohammed Ali; Miraj, Perdana; Sari, Mustika (UI Scholars Hub, 2022)
Technology has long been regarded to be one of the key drivers of economic growth and a major contributor to a nation's competitiveness. Technology is seen as a significant instrument for increasing the value of a product, project, or service while using the same amount of available resources or capital. Rapid technological improvement and invention have contributed to more efficient and innovative output in a variety of areas, including but not limited to construction, healthcare, energy, tourism, and manufacturing. However, many industries are currently under intense pressure to reduce their use of energy, material, and other non-renewable energy resources. The public and society are also demanding practical solutions for addressing sustainability and climate change issues while also improving people's quality of life. Combining technologies and the circular economy concept within the project life cycle is one approach to these issues. The circular economy concept is based on using as few resources as possible and ensuring that materials used during, for example, the manufacturing process are reused, recycled, or repurposed before becoming product waste. The concept transforms traditional linear economy, also known as open loop systems, in which materials and available resources are reused rather than disposed away, resulting in a closed loop system that allows waste prevention and pollutant emission reduction. Multiple resources, such as plastic, chemicals, metals, and other substances, are frequently used only once before becoming waste. Through various approaches of design development, manufacturing process, technological adoption, and system modification throughout the product life cycle, the circular economy ensures that these materials are preserved in their optimum value for as long as possible. Numerous technologies can be employed, combined, and deployed to assist the circular economy throughout the project life cycle. For example, the internet of things (IoT) provided automated big data collection through various sensors, which can be utilized to study people's behavior. In the circular economy phase, artificial intelligence ability to perform many functions while processing unstructured data for further analysis is frequently combined with IoT in facilitating the product movement from consumers back to manufacturers. The technologies enable decision makers to identify methods to tackle complicated problems by using specified criteria, rules, and massive amounts of data. Blockchain, a distributed ledger technology, is currently being incorporated from the design and planning stages to better comprehend asset monitoring and management. It provided major benefits to stakeholders by increasing transparency, improving security, improving traceability, increasing efficiency and speed, and lowering costs. The usage of virtual reality is now also being researched to understand how technology may help to raise public awareness of the circular economy and engage individuals in adopting the principles. Furthermore, to aid in the development of these ecosystems, supportive policy design, appropriate financing, and program implementation should be provided. The government public policy should adhere to the principles of circularity. It should be designed to assist and encourage entrepreneurs, organizations, scholars, researchers, government agencies, and other stakeholders to embrace circularity as a new norm for innovating production and consumption systems through technology adoption and new business models. The industrial technology revolution has clearly improved the effectiveness and efficiency of production, management, and governance systems. We believe that research conducted to develop innovative approaches by utilizing emerging technology can promote the advancement of a circular economy while also contributing to tackle sustainability and environmental challenges.